Significance of Alpha-inhibin Expression in Pheochromocytomas and Paragangliomas. (7th September 2021) - Mete, Ozgur; Pakbaz, Sara; Lerario, Antonio M.; Giordano, Thomas J.; Asa, Sylvia L.
Abstract : Alpha-inhibin expression has been reported in pheochromocytomas and paragangliomas (PPGLs). We analyzed alpha-inhibin immunohistochemistry in 77 PPGLs (37 pheochromocytomas [PCCs] and 40 paragangliomas) and correlated the results with catecholamine profile, tumor size, Ki-67 labeling index, succinate dehydrogenase B subunit and carbonic anhydrase IX (CAIX) staining, and genetic pathogenesis. PPGLs were classified as pseudohypoxic cluster 1 disease with documented VHL mutation or SDHx mutation or biochemical phenotype, whereas NF1 -driven and RET -driven PPGLs and those with a mature secretory (adrenergic or mixed adrenergic and noradrenergic) phenotype were classified as cluster 2 disease. The Cancer Genome Atlas data on INHA expression in PPGLs was examined. Alpha-inhibin was positive in 43 PPGLs (56%). Ki-67 labeling indices were 8.07% and 4.43% in inhibin-positive and inhibin-negative PPGLs, respectively ( P <0.05). Alpha-inhibin expression did not correlate with tumor size. Alpha-inhibin was expressed in 92% of SDHx -related and 86% of VHL -related PPGLs. CAIX membranous staining was found in 8 of 51 (16%) tumors, including 1 SDHx -related PCC and all 5 VHL -related PCCs. NF1 -driven and RET -driven PPGLs were negative for alpha-inhibin and CAIX. Alpha-inhibin was expressed in 77% of PPGLs with a pseudohypoxia signature, and 20% of PPGLs without a pseudohypoxia signature ( P <0.05). PPGLs with a mature secretory phenotype were negative for CAIX. The Cancer Genome Atlas data confirmed higher expression of INHA in cluster 1 than in cluster 2 PPGLs. This study identifies alpha-inhibin as a highly sensitive (90.3%) marker for SDHx/VHL -driven pseudohypoxic PPGLs. Although CAIX has low sensitivity, it is the most specific biomarker of VHL -related pathogenesis. While alpha-inhibin cannot replace succinate dehydrogenase B subunit immunohistochemistry for detection of SDHx -related disease, it adds value in prediction of cluster 1 disease. Importantly, these data emphasize that alpha-inhibin is not a specific marker of adrenal cortical differentiation, as it is also expressed in PCCs.